The Arab-Israeli conflict and the Knesset’s position on it 1966 - 1967 - Dr. Jassim Muhammad Shaghit Al-Kaabi, (Journal of College of Education, 2025)
The Arab-Israeli conflict in the sixties of the last century witnessed a new phase, represented by the military operations carried out by the Palestinian guerrillas, which were met on the other side by the Israeli army’s response and military operations in the border areas in Jordan and Syria. The Arab-Israeli conflict reached its peak during that period with the outbreak of the June 1967 war. These developments were reflected in the discussions of the (Israeli) Knesset.
Keywords: Israel, the Knesset, the June War